Acute appendicitis in pregnancy: a diagnostic and management challenge - Zainuddin, Zainur Rashid; Aznal, Suhaila; Md Nor, Azmi (International Islamic University Malaysia, 2014)
Acute appendicitis is the most common extra-uterine surgical emergency encountered during pregnancy, but an accurate diagnosis is still an enigma. Anatomical shifting of the appendix by the enlarging uterus makes the clinical and sonographic diagnosis difficult. Prompt diagnosis and treatment are essential to prevent perforation, which increases the risk of fetal and maternal death. Surgical intervention, either by an open laparotomy or laparoscopy is the most appropriate treatment for appendicitis. This article reviews the epidemiology, clinical diagnosis, investigation, complications and treatment of acute appendicitis in pregnancy.